2005
DOI: 10.1007/s00468-005-0435-2
|View full text |Cite
|
Sign up to set email alerts
|

Interactive effects of elevated CO2 and drought stress on leaf water potential and growth in Caragana intermedia

Abstract: We studied the responses of leaf water potential ( w ), morphology, biomass accumulation and allocation, and canopy productivity index (CPI) to the combined effects of elevated CO 2 and drought stress in Caragana intermedia seedlings. Seedlings were grown at two CO 2 concentrations (350 and 700 µmol mol −1 ) interacted with three water regimes (60-70%, 45-55%, and 30-40% of field capacity of soil). Elevated CO 2 significantly increased w , decreased specific leaf area (SLA) and leaf area ratio (LAR) of drought… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 52 publications
2
6
1
Order By: Relevance
“…Relatively low photosynthesis rate in the leaves of S. superba grown with the low N treatment and elevated CO 2 concentration in the later measurement period also supported the finding. During our measurement, O. pinnata growth was not affected by the CO 2 concentration treatments, which is contrary with most of previous studies where tree growth was positively affected by elevated CO 2 concentration (Xiao et al 2005;Ceulemans et al 1996;Sefcik et al 2007). However, we hypothesized that the greater growth would soon be found for the O. pinnata grown with the elevated CO 2 concentration as downregulation of photosynthesis was not found for this species.…”
Section: Discussioncontrasting
confidence: 84%
“…Relatively low photosynthesis rate in the leaves of S. superba grown with the low N treatment and elevated CO 2 concentration in the later measurement period also supported the finding. During our measurement, O. pinnata growth was not affected by the CO 2 concentration treatments, which is contrary with most of previous studies where tree growth was positively affected by elevated CO 2 concentration (Xiao et al 2005;Ceulemans et al 1996;Sefcik et al 2007). However, we hypothesized that the greater growth would soon be found for the O. pinnata grown with the elevated CO 2 concentration as downregulation of photosynthesis was not found for this species.…”
Section: Discussioncontrasting
confidence: 84%
“…Markesteijn and Poorter (2009) suggested that an increase in S/R may occur to maximize growth under stress conditions. A significant increase in RMF in the TEMPx f CO 2 and TEMP treatments compared to ambient conditions was also reported by Xiao et al (2005) and Raizada et al (2009). For example, Raizada et al (2009) found a greater RMF when Caragana intermedia Kuang and H.C. Fu was exposed to 700 ppm, and suggested that this may indicate insufficient nutrient availability.…”
Section: Tree Seedling Growthsupporting
confidence: 68%
“…An increase in the S/R ratio for both tree species in the TEMP, f CO 2 and TEMPx f CO 2 treatments compared to AMB conditions was also reported in other studies (Wilson 1988;Shenglei and Ferris 2006;Xiao et al 2005;Overdieck et al 2007;Allen and Vu 2008). Markesteijn and Poorter (2009) suggested that an increase in S/R may occur to maximize growth under stress conditions.…”
Section: Tree Seedling Growthsupporting
confidence: 57%
See 2 more Smart Citations